Truth matters: the BBC and our need for it to be right - Lloyd, J (Reuters Institute for the Study of Journalism, 2012)
The scandals which erupted within the BBC in November 2012 posed questions about the governance and the management culture of the BBC. In this report we illuminate the major areas of contention and debate, show what the underlying and often long-running problems in the management structure are and point to the main routes of future developments now in discussion within and about the BBC.